Faktor Pendorong dan Penghambat Implementasi Kebijakan Pusat Kontrol Penegakan Pelanggaran Elektronik Lalu Lintas - Panji Gedhe Prabawa; Hardi Warsono; Ida Hayu Dwimawanti (PERSPEKTIF, 2021)
This research explains the driving and inhibiting factors and has the aim to describe and analyze the driving and inhibiting factors in implementing E-ticketing policy in Semarang City. This research was prepared using qualitative methods that describe the phenomenon of policy implementation such as: communication, resources, disposition and bureaucratic structure. The results showed the implementation of the E-Traffic Policy in Semarang City in 2019 had not been going well and was fast overall. This aspect can be seen from: policy communication is not going well, the implementer does not need approval and the community lacks information on how E-Tilang is implemented. Public policy resources that have been published, human resources, authority, infrastructure, information resources and authority, but still not optimal. Aspects related to good employee relations, do not yet exist in the public bureaucracy do not yet support. The driving factors are leadership support, adequate resources, staff readiness, and community support. The inhibiting factor is the need for time to determine policy, fragmentation, community misunderstanding and wrong perception.